Administrative Data Processing Applications Fuel (BBM) and at the pump 34-15142 Lubricant Oil using Visual Basic 6.0 Programming Languages - Bahri Bahri; Eriek Orlando (Jurnal Sistem Informasi, 2010)
In a company or organization, a business development company became abenchmark for the success of these companies. To keep the permonmance of thecompany, it should be able to mobilize all the resources to maximize itsoperational work. One of them is in need of application program for managingand cultivating existing data. Its because to make a right decision needs datawhich is accurate and easily to understood. Here the role of database applicationprograms as the provision of computerized data are able to provide informationin a short time and easy to read. The author takes the case to the General FuelFilling Station (Gas Station), namely Nusa Indah Gas Stations 34-15142. It stillusing manual process in recording, counting and making sales report everymonth, therefore the use of a computerized system is expected to accelerate thework and resolve problems, supported by the speed of data processing andaccuracy of the data result. The author tries to design administrative dataprocessing applications of fuel and lubricating oil using Visual Basic 6.0. andMicrosoft Access.